Compliant Robotics in Space: A Prospective Review of Soft and Deformable Systems for Space Missions - Hamed Rahimi Nohooji; Holger Voos (Advanced Intelligent Systems, 2025)
Space exploration demands innovative robotic solutions to address complex challenges. This article provides a forward‐looking perspective on the emerging field of compliant robotics for space applications, categorizing these systems into reconfigurable, hyper‐redundant, origami‐inspired, and soft robots, each offering unique advantages and facing distinct challenges. The review explores in‐depth the critical roles these compliant robots can assume, ranging from on‐orbit servicing to planetary exploration and beyond. It also addresses material selection, accounting for the harsh conditions of space, and examines the complexities in design, actuation, sensing, and control. The article concludes with a future‐focused discussion of emerging trends, challenges, and research directions. This review aims to offer a comprehensive understanding of the current state of the art, positioning compliant robotics as a transformative force in the next frontier of space exploration.